The Effects of Principal’s Competence and School’s Culture on Student’s Character Development - Sumargiono, Sumargiono; Arafat, Yasir; Rahman, Andi (Graduate Program Magister Manajemen Pendidikan, 2022)
This study focuses on the impact of the principal's competence and school’s culture on student’s character development partially and simultaneously. This study uses quantitative methodologies. The academic community of State Elementary Schools in Air Kumbang District, Banyuasin Regency, is the population of this study. A sample of 123 third-grade kids is drawn to reflect the research data. We employ the entire population as a purposive sample. Questionnaires, observations, and documentation were used to collect data. The study hypotheses were evaluated and assessed utilizing basic and multiple linear regression tests to examine the data. The result showed that the principal's competence and school’s culture both impact the student's character development.